The golden road : how ancient India transformed the world - Dalrymple, W. (b)
India is the forgotten heart of the ancient world. In the millennium and a half from c. 250 BC to 1200 AD, Indian art, religion, technology, astronomy, music, dance, literature, mathematics and mythology blazed a trail across the world - a Golden Road that stretched from the Red Sea to the Pacific. Like ancient Greece, ancient India came up with a set of profound answers to the big questions about what the world is, how it operates, why we are here and how we should live our lives. Today, over half the world's population lives in areas where Indian religions and culture are, or once were, dominant. The Golden Road reveals how Indian ideas transformed the world, crossing political borders to influence everything from the statues of Indian ascetics in Roman seaports to Buddhism in Japan, and the observatories of Baghdad to crucial mathematical concepts such as 'zero' - and even the very numbers we use to this day. Drawing from a lifetime of scholarship, award-winning historian William Dalrymple argues that India is one of the two great intellectual and philosophical superpowers of Asia
Includes index.